2020
DOI: 10.1002/cam4.3352
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome predicts postoperative complications after gastrectomy in gastric cancer patients: Development of an individualized usable nomogram and rating model

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 28 publications
0
17
0
2
Order By: Relevance
“…The presence of MetS increases the risk for postoperative complications, including prolonged hospital stay and risk for postsurgical complications (OR, 1.20 [95% CI, 1.03–1.09] and 1.22 [95% CI, 1.09–1.37] for patients with breast and prostate cancer with MetS undergoing tumor removal, respectively), blood transfusion, surgical site infection, and respiratory failure, across various surgical populations. 246,270–274…”
Section: Metabolic Syndromementioning
confidence: 99%
“…The presence of MetS increases the risk for postoperative complications, including prolonged hospital stay and risk for postsurgical complications (OR, 1.20 [95% CI, 1.03–1.09] and 1.22 [95% CI, 1.09–1.37] for patients with breast and prostate cancer with MetS undergoing tumor removal, respectively), blood transfusion, surgical site infection, and respiratory failure, across various surgical populations. 246,270–274…”
Section: Metabolic Syndromementioning
confidence: 99%
“…Accordingly, a total of 1248 (18.8%) patients had MetS at baseline. The follow-up durations were within hospitalization for studies reported the outcome of postoperative complications only 13 17 , and varied from 35 to 75 months for studies reporting the outcomes of overall mortality and cancer recurrence. Multivariate models were applied to analyze the associations between MetS and clinical outcomes of patients with GC, and possible confounding factors such as age, sex, tumor characteristics, and other anticancer therapies etc.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 549 articles were excluded since their titles and abstracts were not relevant to the meta-analysis, leaving 24 studies in total for the full-text review. Finally, after excluding 16 studies through full-text review, eight studies [13][14][15][16][17][18][19][20] were included. The reasons for the removing of the 16 studies are also presented in ▶ Fig.…”
Section: Studies Obtainedmentioning
confidence: 99%
See 2 more Smart Citations